PENGARUH KOMPETENSI APARATUR, SYSTEM PENGENDALIAN INTERN DAN MORALITAS INDIVIDU TERHADAP PENCEGAHAN FRAUD DANA DESA - Yusdhaniar; Yusuf, Marwah; Ibrahim, Irmawati; Indah Waty, Fulia (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
Abstract This research was conducted to find out the Effect of Apparatus Competence, Internal Control System and Individual Morality on Prevention of Village Fund Fraud in the Village Government in the Middle Adonara district. This research is a survey research using a questionnaire. The population taken in this study amounted to 35 people. The sample taken for this study amounted to 65 respondents, but of the 65 questionnaires that were distributed only 35 were returned and 30 were not returned so that the number of questionnaires processed was 35. This sample was taken using a saturated sampling method. Hypothesis testing is carried out using multiple lenear regression techniques. The results of this study state that Apparatus Competence, Internal Control System and Individual Morality have a significant effect on the prevention of Village Fund Frauds in the Village government in the Middle Adonara District. Keywords: apparatus competence, internal control system, and individual morality